Melanotic Neuroectodermal Tumor of Infancy: A Clinicopathological and BRAF V600E Mutation Study of 11 Cases - Xia, Rong-Hui; Zhang, Chun-Ye; Wang, Li-Zhen; Hu, Yu-Hua; Sun, Jing-Jing; Tian, Zhen; Li, Jiang (Frontiers in Oncology, 2021)
Purpose To investigate the clinicopathological features and BRAF V600E mutation of melanotic neuroectodermal tumor of infancy (MNTI). Materials and Methods Eleven cases of MNTI diagnosed at the Department of Oral Pathology were collected. Clinicopathological characteristics were obtained from the medical records. Immunostaining was performed by immunohistochemistry (IHC). Amplification-Refractory Mutation System-qPCR (ARMS-qPCR) and Sanger Sequencing were used to detect BRAF V600E mutation. Results Of the 11 cases, 3 cases were female and 8 cases were male. The mean age of the first symptoms was 3.2 months (range: 1 to 6 months). Ten cases (90.9%) located in maxilla but only one (9.1%) in mandible. Most of the cases demonstrated well-defined mass with lytic bone destruction and tooth germ affecting radiologically. Histologically, MNTI was consisted of large polygonal melanin-producing epithelioid cells and small round neuroblast-like cells which arranged in irregular alveolar, tubuloglandular and fissured architecture. The epithelioid cells expressed Vim, Pan-CK, NSE and HMB45, while the smalls cells expressed Syn, NSE and scattered Vim. Most cases showed low Ki-67 index (range: <1% to 50%). None of the MNTI cases showed BRAF V600E mutation. Most cases were treated with enucleation (45.4%) or curettage (36.4%). Among the 11 cases, 6 cases had follow-up information, and 2 cases had recurrence lesions after surgery. Conclusion MNTI, an extremely rare tumor, mainly affects male infants with strong preference for maxilla. Distinct histopathological features and immunohistochemical profile are helpful to distinguish from other melanin-containing tumors and small round cell tumors. No BRAF V600E mutation in MNTI is detected in the present study and needs further investigations. The factors that contribute to the local recurrence of MNTI are controversial, but the close follow-up for the patients is recommended.